Analysis of ecological benefits of agricultural land and design of evaluation strategies - Gao, Menghui; Noh, Nur Ilya Farhana Md; Lin, Ng Jing (Edelweiss Applied Science and Technology, 2024)
The rational application of farmland resources is the basis of China's social and economic development, and in the context of global low-carbon and sustainable development strategies, the rational allocation of farmland resources and the analysis of ecological benefits are particularly important. In this regard, this study constructs an evaluation strategy for ecological benefit analysis of farmland based on the theory of low carbon economy and the theory of carbon emission from farmland. Firstly, the farmland analysis indexes are determined, including land ecological conditions, land environmental quality and ecological environment at three levels; then the entropy value method and the coefficient of variation method are used to obtain the set weights of each index; finally, the comprehensive index evaluation formula is relied on to obtain the results of farmland eco-efficiency in each region. The experimental data show that the method can effectively improve the accuracy of the evaluation strategy and has a higher practical scope.